Appendectomy and risk of Parkinson’s disease: a systematic review and meta-analysis - Hok Leong Chin; Yiu Sing Tsang; Haojun Shi (Frontiers in Neurology)
IntroductionBraak’s hypothesis suggests that α-synuclein may enter the central nervous system through the enteric nervous system and contribute to the pathogenesis of Parkinson’s disease (PD). The appendix, enriched in α-synuclein, has been proposed as a possible entry point in PD pathogenesis. This systematic review and meta-analysis aimed to assess the association between appendectomy and PD risk using newly available data.MethodsA literature search was conducted in PubMed and Embase through September 10, 2024, to identify studies on appendectomy and PD risk. Two independent reviewers screened and assessed articles for eligibility with a third reviewer involved in cases of disagreement. Study quality was assessed using the Newcastle-Ottawa Scale. Data for meta-analysis were pooled using a random-effects model and analyzed in Review Manager 5.4. Meta-regression, subgroup, and sensitivity analyses were performed.ResultsNine studies met inclusion criteria. Meta-analysis indicated no significant association between appendectomy and PD risk (RR: 1.01, 95% CI: 0.90–1.12, p = 0.89). Subgroup analyses showed similar findings. Sensitivity analyses did not change the estimate.ConclusionThis analysis suggests no association between appendectomy and PD risk.